Genetic Evidence on the Origins of Indian Caste Populations - Bamshad, Michael; Kivisild, Toomas; Watkins, W. Scott; Dixon, Mary E.; Ricker, Chris E.; Rao, Baskara B.; Naidu, J. Mastan; Prasad, B.V. Ravi; Reddy, P. Govinda; Rasanayagam, Arani; Papiha, Surinder S.; Villems, Richard; et al. (Genome Research, 2001)
The origins and affinities of the ∼1 billion people living on the subcontinent of India have long been contested. This is owing, in part, to the many different waves of immigrants that have influenced the genetic structure of India. In the most recent of these waves, Indo-European-speaking people from West Eurasia entered India from the Northwest and diffused throughout the subcontinent. They purportedly admixed with or displaced indigenous Dravidic-speaking populations. Subsequently they may have established the Hindu caste system and placed themselves primarily in castes of higher rank. To explore the impact of West Eurasians on contemporary Indian caste populations, we compared mtDNA (400 bp of hypervariable region 1 and 14 restriction site polymorphisms) and Y-chromosome (20 biallelic polymorphisms and 5 short tandem repeats) variation in ∼265 males from eight castes of different rank to ∼750 Africans, Asians, Europeans, and other Indians. For maternally inherited mtDNA, each caste is most similar to Asians. However, 20%–30% of Indian mtDNA haplotypes belong to West Eurasian haplogroups, and the frequency of these haplotypes is proportional to caste rank, the highest frequency of West Eurasian haplotypes being found in the upper castes. In contrast, for paternally inherited Y-chromosome variation each caste is more similar to Europeans than to Asians. Moreover, the affinity to Europeans is proportionate to caste rank, the upper castes being most similar to Europeans, particularly East Europeans. These findings are consistent with greater West Eurasian male admixture with castes of higher rank. Nevertheless, the mitochondrial genome and the Y chromosome each represents only a single haploid locus and is more susceptible to large stochastic variation, bottlenecks, and selective sweeps. Thus, to increase the power of our analysis, we assayed 40 independent, biparentally inherited autosomal loci (1 LINE-1 and 39 Aluelements) in all of the caste and continental populations (∼600 individuals). Analysis of these data demonstrated that the upper castes have a higher affinity to Europeans than to Asians, and the upper castes are significantly more similar to Europeans than are the lower castes. Collectively, all five datasets show a trend toward upper castes being more similar to Europeans, whereas lower castes are more similar to Asians. We conclude that Indian castes are most likely to be of proto-Asian origin with West Eurasian admixture resulting in rank-related and sex-specific differences in the genetic affinities of castes to Asians and Europeans.